Catalyst consumption during one and two steps transesterification of crude soybean oils - Pisarello Milesi, Maria Laura (2013)
In this work, the transesterification reaction of refined and crude oils was studied. The reaction was carried out using methanol, with the aim of studying the effect of different catalysts, such as sodium and potassium hydroxides and methoxides, all of them in the same molar concentration. The saponification is an important side-reaction in this system, and was carefully analyzed in order to compare the yields and the rate of soaps formation with each catalyst. Significant differences among them have been found. The catalyst and soaps distribution between the biodiesel and the glycerine phases was also determined. It was found that a very important fraction of the hydroxides, both sodium and potassium, are consumed by the saponification reaction, thus decreasing the final acyl-glycerides conversion. Carrying out the reaction in two steps, it was found that not improvement was obtained regarding the catalyst consumption and soap formation, what indicates that the water fed to the system and the water formed by free fatty acid neutralization, determine these values independently of the reaction strategy followed in the process. The importance of this study is that in medium and small scale plants, the biodiesel production is often carried out with crude oils, and consequently, the selection of the catalyst that minimizes soap formation and its solubility in the biodiesel phase, is an important issue.